GREEN FACTOR OF ECONOMIC GROWTH IN UZBEKISTAN (PROBLEMS AND PROSPECTS) - Saidkamolkhon Bakhodirov; Daniel Korjakov (European Science Publishing, 2023)
The article discusses the features, problems and prospects of the green factor of economic growth in Uzbekistan, analyzes international experience in the transition to a green economy, and also describes the main directions of development of the green economy in the Republic of Uzbekistan.